Synthesis of Leaf-spring Suspension Parameters for High-comfort Vehicles - Maksimov, Roman O.; Chetverikov, Mikhail V.; Rubanov, Pavel S.; Mavlonov, Mirzoodil H.; Zhileykin, Mikhail M.; Keller, Andrey V.; Shadrin, Sergey S.; Makarova, Daria A.; Furletov, Yury M. (Automotive Experiences, 2025)
This paper develops the new leaf-spring suspension parameters synthesis methods based on the use of modern mathematical and computer modeling tools to provide vehicle high in-motion comfort. The research aims to develop the new loading characteristics and design parameters synthesis methodology for the vehicle suspension system components, exactly for the elastic element (leaf-spring), the damping element (hydraulic shock absorber) and the transverse stabilizer bar. The authors demonstrate approaches to the use of vehicle dynamics simulation modeling, topological and parametric optimization, and finite element method and explain their role in the new developed vehicle leaf-spring suspension system parameters synthesis methodology. As main results, the authors propose a formation method for a primary suspension system elastic element non-linear loading characteristic to provide for the in-motion vehicle comfort. They develop a synthesis technique for the variable profile longitudinal section geometry of a leaf-spring and its other design parameters to generate the loading characteristic close to the one required for high motion comfort. They also proposed a loading characteristics synthesis for the damping element of the primary suspension with a leaf-spring-type elastic element and selection the most suitable one for a specific vehicle method. The authors also propose a stiffness calculation procedure for a randomly shaped transverse stabilizer bar when selecting its design parameters. As a contribution, based on the comparative virtual tests results of the motion comfort indicators of a vehicle with the loading characteristics generated using the developed methodology for the primary leaf-spring suspension and the initial basic configuration of the classic leaf-spring suspension, it was recorded that the vehicle motion comfort improved by 10-25% when the developed synthesis methodology was used.